Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pntd.0010332
|View full text |Cite
|
Sign up to set email alerts
|

Infection intensity-dependent accuracy of reagent strip for the diagnosis of Schistosoma haematobium and estimation of treatment prevalence thresholds

Abstract: Background Reagent strip to detect microhematuria as a proxy for Schistosoma haematobium infections has been considered an alternative to urine filtration for individual diagnosis and community-based estimates of treatment needs for preventive chemotherapy. However, the diagnostic accuracy of reagent strip needs further investigation, particularly at low infection intensity levels. Methods We used existing data from a study conducted in Tanzania that employed urine filtration and reagent strip testing for S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Participant age, sex, infection intensity [ 30 ], and S haematobium prevalence [ 29 ] may affect urine reagent strip test performance. Before sample selection for this study, the overall prevalence of Schistosoma infection in the BILHIV study was 5.5% by urine microscopy, thus meeting World Health Organization classification of a low-risk community [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participant age, sex, infection intensity [ 30 ], and S haematobium prevalence [ 29 ] may affect urine reagent strip test performance. Before sample selection for this study, the overall prevalence of Schistosoma infection in the BILHIV study was 5.5% by urine microscopy, thus meeting World Health Organization classification of a low-risk community [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of diagnostics probably varies by setting and is affected by disease prevalence and infection intensity. 16 , 164 Previous meta-analyses have found that, independent of prevalence, haematuria reagent strips performed better in school-aged children than in adults. 139 , 146 …”
Section: Discussionmentioning
confidence: 99%
“…While this observation warrants close monitoring in the following study years, since increasing (trace) microhematuria might be a first sign of infections and recurrent morbidity in individuals missed by the 5T interventions, our current assumption is that the increase in trace microhematuria was caused by different and newer batches of Hemastix that were started to be used after the baseline survey in 2021. Other studies from Pemba and Tanzania mainland confirm that older/expired strips have a less intense color reaction [ 24 ] and recommend that trace results should be considered negative for S. haematobium infections when a high specificity is aimed for in settings with low egg counts in urine filtration [ 25 ].…”
Section: Discussionmentioning
confidence: 99%